2022
DOI: 10.1088/1361-6501/ac7b12
|View full text |Cite
|
Sign up to set email alerts
|

Measurement method of a microspring-supported force plate with an external laser displacement meter

Abstract: Ground reaction force (GRF) is a significant factor for the evaluation of animal locomotion. Recently, micro force plates have been implemented as the GRF measurement method for tiny insects. Previous micro force plates were highly sensitive but fragile and laborious to fabricate because of the use of strain-sensing elements. Here, we applied high-resolution 3D printing and a noncontact displacement meter to a micro force plate for a fruit fly. A force plate structure with 3D supporting microsprings is fabrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…However, there is a limit to realizing a small spring constant so that the force plate deforms under its own weight, similar to our developed device. Compared to the spring constant of previously 3D-printed highly sensitive force plate with a spring constant of 5.98 N/m [ 19 ], that of our developed device was approximately 30 times lower.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…However, there is a limit to realizing a small spring constant so that the force plate deforms under its own weight, similar to our developed device. Compared to the spring constant of previously 3D-printed highly sensitive force plate with a spring constant of 5.98 N/m [ 19 ], that of our developed device was approximately 30 times lower.…”
Section: Discussionmentioning
confidence: 73%
“…Theoretically, the displacement of the plate center remains the same regardless of where the force is applied. In practice, displacement may vary depending on the location of the applied force [ 19 ]. We experimentally evaluated the distribution of the spring-constant error of the force plate.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, the GRF vibration in the direction of gravity was several tens of the percent of body weight. In contrast, GRF measurements of a fruit fly, which was similar in weight to ants, indicated little vibration during walking [21]. Therefore, it is suggested that the slight vibration in the direction of gravity is a characteristic of the mg-order insect's gait.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, force plates using different measurement principles have been developed for fruit flies. These plates consist of a plate structure supported by mechanical springs and a laser displacement sensor [21][22][23]. The plate has a sufficiently large area to measure the total GRF while the fly is walking.…”
Section: Discussionmentioning
confidence: 99%